1984
DOI: 10.1111/j.1545-5300.1984.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Evaluation of Family Therapy Training

Abstract: As the first substantive use of the FTCS, some useful information about the coding system emerged from this study. Its unitization and categorization reliability proved to be excellent. The results supported the discriminant validity of certain subscales, which confirmed predicted differences and distinguished trainees at varied levels of experience. In general, the continued use of the FTCS for the evaluation of therapy and training appears to be highly desirable. Three hypotheses were examined to account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…Little is yet known for certain of the implied links between conceptual change and therapeutic effectiveness (Tucker and Pinsof, 1984) and such postulation is well beyond the scope of this paper. Rather, N and D illustrate the idiosyncratic fashion in which trainee family therapists will seek to make sense of their training experience.…”
Section: Indiuidual Tale5mentioning
confidence: 99%
“…Little is yet known for certain of the implied links between conceptual change and therapeutic effectiveness (Tucker and Pinsof, 1984) and such postulation is well beyond the scope of this paper. Rather, N and D illustrate the idiosyncratic fashion in which trainee family therapists will seek to make sense of their training experience.…”
Section: Indiuidual Tale5mentioning
confidence: 99%
“…Given that there are these two distinctly different paths for entering family therapy training, the differences produced by these two approaches to acquiring therapeutic skills is an issue which needs to be addressed in the future. This is particularly the case as Tucker and Pinsof (1984) also produce some evidence that pre-experience of family interviewing had some effect on the outcome of in-therapy behaviour in that those with prior experience performed more ably than those who did not have such experience.…”
Section: Personnel Studiesmentioning
confidence: 95%
“…Bishop et al, 1984), to those that are multi-professional and presumably multicontextual (e.g. Tucker and Pinsof, 1984). The Bishop et al course, being confined to a single agency, was well able to set context objectives and the follow-up study on this course (Byles et al, 1983) found that the number of family interviews throughout the agency increased.…”
Section: E Streetmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) There are several instruments for studying trainee performance which have 'some degree of validity and reliability' (for example, the Family Therapist Coding System (Tucker and Pinsof, 1984), the Family Rating Scale ) and a Training Evaluation Instrument (Breunlin et al, 1983). (b) There is evidence that various forms of training can produce an improvement in cognitive and intervention skills, although the latter is less certain because intervention skills have never been measured in actual therapy sessions (Zaken-Greenberg and Neimeyer, 1986).…”
mentioning
confidence: 99%